Komposisi dan Struktur Vegetasi Pohon pada Habitat Rafflesia arnoldii R.Br. di Kawasan Hutan Nagari Saniangbaka, Kabupaten Solok - Chairul, Chairul; Najah, Muthiya Safinatun (Jurnal Biologi Universitas Andalas, 2025)
The research on the composition and structure of tree vegetation in the habitat of Rafflesia arnoldii R.Br. in the Saningbaka Forest area, X Koto Singkarak District, Solok Regency, was conducted from March to July 2024.The objective of this study was to ascertain the composition and structure of tree vegetation in the habitat of Rafflesia arnoldii. Vegetation analysis was performed using purposive sampling along a 50 x 20 m transect, with ten subplots measuring 10 x 10 m each. The results revealed a total of 49 individuals, 18 species, 14 genera, and 11 families were identified, with the dominant families being Urticaceae (34.7%) and Meliaceae (20.4%). Meanwhile, the Euphorbiaceae family (10.2%) was identified as the co-dominant family at this study location. The highest Importance Value Index (IVI) was found for the species Villebrunea rubescens (102.4%), while the lowest IVI was for Mallotus peltatus (5.79%). The diversity index at the study site was classified as moderate, with H' = 2.43. Two buds and six individual flowers of Rafflesia arnoldii were observed in the late blooming phase. The Tetrastigma species identified in the study area was T. leucostaphylum.